2001
DOI: 10.1136/jnnp.70.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stimuli triggering attacks of paroxysmal dystonia induced by exertion

Abstract: In a patient with a familial form of paroxysmal exertion induced dyskinesia (PED), the eYcacy of diVerent stimuli and manoeuvres in triggering dystonic attacks in the arm was studied. As a new approach, transcranial magnetic stimulation (TMS) of the motor cortex was used to trigger motor paroxysms and to monitor cortical excitability during attacks. Motor paroxysms could be provoked by muscle vibration, passive movements, TMS, magnetic stimulation of the brachial plexus, and electrical nerve stimulation. Sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These PKDs were triggered by changing of clothes or diapers or by lifting the children from one place to another. Rarely, induction of PxDs by sensory stimuli or by passive limb movements has been described in other conditions [17,18]. We presume that in our patients the somatosensory stimulus precipitates the PxD, but we are not able to exclude that proprioception may play a pivotal role.…”
Section: Discussionmentioning
confidence: 77%
“…These PKDs were triggered by changing of clothes or diapers or by lifting the children from one place to another. Rarely, induction of PxDs by sensory stimuli or by passive limb movements has been described in other conditions [17,18]. We presume that in our patients the somatosensory stimulus precipitates the PxD, but we are not able to exclude that proprioception may play a pivotal role.…”
Section: Discussionmentioning
confidence: 77%
“…Outside the attacks, cortical excitability and inhibitory neuronal mechanisms (response threshold and amplitudes, duration of the silent period ipsilaterally and contralaterally, corticocortical inhibition and facilitation) have been found to be normal,50 in contrast with focal task‐related dystonia, where abnormal motor cortex inhibition is also present during isometric muscle contraction 51. SPECT studies during motor attacks52 revealed reduced perfusion of the frontal cortex and basal ganglia and increased perfusion of the cerebellum, a SPECT pattern compatible with other forms of idiopathic and symptomatic forms of dystonia 52…”
Section: Paroxysmal Exercise‐induced Dyskinesia (Ped)mentioning
confidence: 99%
“…Surprisingly, and in contrast to paroxysmal exercise-induced dystonia [3], proprioceptive and somatosensory afferent inputs by magnetic stimulation of the brachial plexus or of the biceps brachii did not provoke a seizure. This may indicate that the stimuli has a very specific temporal pattern to induce a seizure.…”
mentioning
confidence: 85%